ANATOMY OF VETTING – BETWEEN LAW AND POLITICS - Perić Diligenski, Tijana D. (Srpska politička misao, 2025)
The paper examines the phenomenon of vetting in the judiciary in Albania, Bosnia and Herzegovina, and Serbia, as post-communist countries in the European Union accession process. Vetting is not a uniform concept, and it appears in several forms, such as review, reevaluation, and re-election (reappointment) of judges. There is no unique vetting model because it is impossible to apply it to different socio-political contexts. The author of this paper approaches vetting as an anti-corruption instrument useful in systems in which the rule of law is systematically and continuously violated, as well as the independence of judges and public prosecutors is violated. Vetting as a personnel reform programme in the judiciary should be agreed upon by a broad consensus (social, legal, and political actors) based on the constitutional and international norms. As a form and the cornerstone of administrative justice, vetting paradigm experienced a Copernican turn from transitional regimes to weak democracies. In the first case, it was a transitional justice mechanism, while in the second case, it was an instrument of recovery and strengthening the rule of law.